(untitled) - Yeo, Richard R. (Cambridge UK, 2001)
Encyclopaedic Visions provides a major contribution to Enlightenment studies, the history of science, and the history of ideas in general. Richard Yeo places these scientific dictionaries in a rich cultural framework of debate that includes the classification of knowledge, the tradition of commonplaces, the Republic of Letters, the Enlightenment public sphere, copyright issues, and the specialization of science.
Keywords: Science,Encyclopedias and dictionaries,Khoa học; History,Encyclopedias,History and criticism,History and criticism,Lịch sử,Bạch khoa toàn thư,Lịch sử và phê bình